2014
DOI: 10.1128/aem.01941-14
|View full text |Cite
|
Sign up to set email alerts
|

Decoration of Outer Membrane Vesicles with Multiple Antigens by Using an Autotransporter Approach

Abstract: iOuter membrane vesicles (OMVs) are spherical nanoparticles that naturally shed from Gram-negative bacteria. They are rich in immunostimulatory proteins and lipopolysaccharide but do not replicate, which increases their safety profile and renders them attractive vaccine vectors. By packaging foreign polypeptides in OMVs, specific immune responses can be raised toward heterologous antigens in the context of an intrinsic adjuvant. Antigens exposed at the vesicle surface have been suggested to elicit protection s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 67 publications
5
90
0
Order By: Relevance
“…Furthermore, the ability of OMVs to activate the innate immune system 14,20,22,24,25,69,114 , together with their particulate nature, provides these nano particles with their own adjuvant activity, as they are able to enhance antibody and T cell responses to antigens 76,83,87,115 . Finally, OMVs are very versatile as they can be bioengineered to express any chosen antigen 77,112,[116][117][118] and they can be manipulated to reduce their endotoxicity [119][120][121] . Despite the enormous vaccine potential of OMVs, it has taken more than 20 years for an OMV-based vaccine to be licensed for human use.…”
Section: Development Of Vaccines Using Omvsmentioning
confidence: 99%
“…Furthermore, the ability of OMVs to activate the innate immune system 14,20,22,24,25,69,114 , together with their particulate nature, provides these nano particles with their own adjuvant activity, as they are able to enhance antibody and T cell responses to antigens 76,83,87,115 . Finally, OMVs are very versatile as they can be bioengineered to express any chosen antigen 77,112,[116][117][118] and they can be manipulated to reduce their endotoxicity [119][120][121] . Despite the enormous vaccine potential of OMVs, it has taken more than 20 years for an OMV-based vaccine to be licensed for human use.…”
Section: Development Of Vaccines Using Omvsmentioning
confidence: 99%
“…Although most autodisplay work has been conducted in E. coli , a few research groups have validated the use of autotransporter‐based surface display in alternative organisms (Tozakidis et al ., ). Recent studies have extended the basic concept of autodisplay and shown that polypeptides fused to autotransporters can also be presented on the surface of OM vesicles and bacterial ghosts (Daleke‐Schermerhorn et al ., ; Hjelm et al ., ). Taken together, the numerous examples of autodisplay that have appeared in the literature demonstrate that a remarkable diversity of polypeptides can be secreted effectively by the autotransporter pathway.…”
Section: Recent Advances In Autodisplaymentioning
confidence: 99%
“…In addition, expressed heterologous proteins that had the ability to anchor to the surface of E. coli cells were also presented on the derived OMVs18. Technologically, fusion with ClyA (a pore-forming hemolytic protein), HBP or AIDA can bring exogenous proteins to the surface of OMVs1920212223. Moreover, exogenous proteins can also be presented in the inner lumen of OMVs by using an appropriate leader protein17.…”
mentioning
confidence: 99%